Stability of a class of adaptive nonlinear systems - Dzieliński, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a research effort focused on the problem of robust stability of the closed-loop adaptive system. It is aimed at providing a general framework for the investigation of continuous-time, state-space systems required to track a (stable) reference model. This is motivated by the model reference adaptive control (MRAC) scheme, traditionally considered in such a setting. The application of differential inequlities results to the analysis of the Lyapunov stability for a class of nonlinear systems is investigated and it is shown how the problem of model following control may be tackled using this methodology.
Keywords: nonlinear systems; Lyapunov stability; adaptive systems